A framework and road map for rapid start-up and completion of a COVID-19 vaccine trial: A single clinical trial site experience - Rojas, Carlos; Spector, Stephen A.; Cale, Bernadette; Loughran, Megan; Lazaro, Leander; Mah, Eric; Firestein, Gary S.; Gold, Kathryn A.; Wallace, Mark (Journal of clinical and translational science, 2022)
The COVID-19 global pandemic required the rapid development of vaccines with a quick start up of phase 1–3 studies with large enrollment targets. The University of California San Diego was identified as a site for the phase 3 trial of the mRNA-1273-SARS-CoV-2 vaccine. There were many challenges with scaling up a large-scale clinical trial in such a short time. This report describes the processes and procedures that were implemented to successfully complete the enrollment target in under 10 weeks. This required the team to identify existing tools that could rapidly be accessed to develop a database, scheduling system, effective communication, document management, staff time tracking/efficiency, subject scheduling/tracking, project management, and accrual/study performance. The outcome of these efforts resulted in rapid enrollment and study completion in a short time. The lessons learned from this experience can be used by other clinical trial sites faced with similar challenges.